The Sick Child Initiative - James Tulloch (Indonesian Pediatric Society, 1997)
Every year some L2 million children die before they reach their fifth birthday, many of them during the first year of life. Seven in every 10 of these child deaths are due to diarrhea, pneumonia, measles, malaria, or malnutrition - and often to a combination of these conditions (see Table 1). In addition to this substantial mortality, these con-ditions typically account for three out of four sick children seeking care at a health facility. Every day, millions of parents seek health care for their children, taking them to hospitals, health centers, pharmacists, community health care providers and traditional healers.